Desain Website UMKM “Kedai Buah dan Oleh-oleh Dayat” Menggunakan Template Website dan Blogger - Saputri, Anggela; Roy Bin Yulius; Syarifah Nur (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
In the digital era, having a website has become a crucial need for Micro, Small, and Medium Enterprises (MSMEs) to enhance visibility and competitiveness. This research aims to explore the process of creating a website for the MSME "Dayat Fruit Stall" using the Blogger platform. The methods used include interviews with the MSME owner to collect data related to products and services, as well as designing a website that focuses on responsive design and easy navigation. The result of this study is a website accessible at https://kedaibuahdayat12.blogspot.com, designed to improve accessibility and customer interaction. This website development demonstrates that by utilizing user-friendly technology, MSMEs can expand their market reach and optimize business operations effectively. In conclusion, online presence through a website is an effective strategy for MSMEs to face competition in the digital age.